Upravljanje javnih podob vodilnih farmacevtskih podjetij na spletnih družbenih omrežjih - Prevolšek, Aljaž (Farmacevtski vestnik, 2021)
Online social network sites provide marketers with a better understanding of patients' needs compared to traditional media, yet research shows that pharmaceutical companies devote less attention to them compared to other industries. We performed a computer-mediated discourse analysis of five blogs and for ten international pharmaceutical companies on three online social network sites. Our research shows that the digital strategy of managing profiles of pharmaceutical online social network sites still trails behind other industries. Leading pharmaceutical companies aren't implementing recommendations for the effective management of profiles on online social network sites consistently. They poorly implement recommendations on the use of sponsored posts, stories, live videos and vertical or square videos. The implementation of recommendations for listing of company data, regular posting and displaying logos in the first three seconds of videos should be more regular to achieve higher engagement rates and better recognition. The most important tool for profile management is video. Pharmaceutical companies pay the most attention to LinkedIn.
Keywords: digitalno trženje; Družbena omrežja; Farmacevtska industrija; Marketing